Kościoły ewangelickie wobec wybranych kwestii międzynarodowych i społeczno-politycznych w Polsce po 1989 roku = Ewangelic churches on selected questions international and socio-political in Poland after 1989 - Krawczyk, Danuta (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents the position of the Protestant environment to a selected number of international issues and socio-political changes in Poland after 1989. The article discusses issuesrelated to Polish-German relations, the Polish accession to NATO and the European Union.
Keywords: Kościół Ewangelicko-Augsburski; Kościół Ewangelicko-Reformowany; Kościół Ewangelicko-Metodystyczny; Polska Rada Ekumeniczna; Wspólna Europa; integracja europejska; posłanie wielkanocne; Dialog po Canberze; Leuenberska Wspólnota Kościołów; antysemityzm; wojna domowa; rezolucja; uchodźca; terroryzm międzynarodowy; homoseksualizm; poronienie sztuczne; eutanazja; Lutheran Church in Poland; Reformed Church in Poland; Evangelical Methodist Chuch in Poland; Polish ecumenical council; Common Europe; European integration; Easter message; Dialog after Canberra; Leuenbersk Community Churches; anti-Semitism; civil war; resolution; refugees; international terrorism; homosexuality; abortion; euthanasia